Basketball in the Key of Law: The Significance of Disputing in Pick‐Up Basketball1. Issue 3 (22nd July 2013) - DeLand, Michael
<x xml:space="preserve">Abstract</x> While the conception of law as a constructive and constitutive force is often stated, we have relatively few concrete and grounded case studies showing precisely where and how social actors construct the meaning of their engagements through the invocation of legality. Drawing on Erving Goffman's Frame Analysis (1974), I use the concept of "keying" to articulate how basketball players in informal "pick‐up" games transform the meaning of their activity through disputing. By playing in a legalistic way, players constitute the game as "real" and "serious" rather than "mere play." The analysis tracks basketball players in the heat of action as they perceive the game, call rule violations, contest those violations, and ultimately give up. Players organize each phase of the dispute's natural history in the "key of law" by constructing and comparing cases, invoking and interpreting rules, setting precedent, arguing over procedure, and proposing solutions. Through these practices, players infuse the game with rich meaning and generate the motivational context demanding that the game be treated as significant. This analysis contributes to an understanding of legal ontology that envisions law's essence as potentiating rather than repairing normative social life.